FLUID trial: a hospital-wide open-label cluster cross-over pragmatic comparative effectiveness randomised pilot trial comparing normal saline to Ringer's lactate. Issue 2 (3rd February 2023) - McIntyre, Lauralyn Ann; Fergusson, Dean A; McArdle, Tracy; Fox-Robichaud, Alison; English, Shane W; Martin, Claudio; Marshall, John; Cook, Deborah J; Graham, Ian D; Hawken, Steven; McCartney, Colin; Menon, Kusum; et al.
Abstract : Objectives: Normal saline (NS) and Ringer's lactate (RL) are the most common crystalloids used for fluid therapy. Despite evidence of possible harm associated with NS (eg, hyperchloremic metabolic acidosis, impaired kidney function and death), few large multi-centre randomised trials have evaluated the effect of these fluids on clinically important outcomes. We conducted a pilot trial to explore the feasibility of a large trial powered for clinically important outcomes. Design: FLUID was a pragmatic pilot cluster randomised cross-over trial. Setting: Four hospitals in the province of Ontario, Canada Participants: All hospitalised adult and paediatric patients with an incident admission to the hospital over the course of each study period. Interventions: A hospital wide policy/strategy which stocked either NS or RL throughout the hospital for 12 weeks before crossing over to the alternate fluid for the subsequent 12 weeks. Primary and secondary outcome measures: The primary feasibility outcome was study fluid protocol adherence. Secondary feasibility outcomes included time to Research Ethics Board (REB) approval and trial initiation. Primary (composite of death or re-admission to hospital in first 90 days of index hospitalisation) and secondary clinical outcomes were analysed descriptively. Results: Among 24 905 included patients, mean age 59.1 (SD 20.5); 13 977 (56.1%) were female and 21 150 (85.0%) had medical or surgical admitting diagnoses. Overall, 96 821 L were administered in the NS arm, and 78 348 L in the RL arm. Study fluid adherence to NS and RL was 93.7% (site range: 91.6%–98.0%) and 79.8% (site range: 72.5%–83.9%), respectively. Time to REB approval ranged from 2 to 48 days and readiness for trial initiation from 51 to 331 days. 5544 (22.3%) patients died or required hospital re-admission in the first 90 days. Conclusions: The future large trial is feasible. Anticipating and addressing logistical challenges during the planning stages will be imperative. Trial registration number: NCT02721485 .